Conflict in Nursing Management in the Hospital Context - Soeli Teresinha GuerraI (2022)
This qualitative study aimed to analyze how conflicts manifest in interpersonal relations and the dimensions they assume in nursing management in hospitals. Data were collected through semi-structured interviews with 13 nurse managers from hospitals in the interior of Rio Grande do Sul, Brazil. Content analysis was used to interpret the results